Tokovne razmere v avtomobilski lakirnici: numerična in eksperimentalna analiza - Marn, Jure (Strojniški vestnik, 2002)
This paper deals with the flow analysis around a car in a spray-paint chamber.To solve Navier-Stokes equations for 3D flow of an incompressible and isothermal fluid we used the control-volume method (CFX 5.4). The numerical procedure, the boundary and initial conditions, the methods used for stabilizing the numerical oscillations as well as the other parameters important for the numerical procedure are described in detail. Result for 2D and 3D calculations are presented. The boundary conditions were determined with measurements in a real chamber with and without a car. The filter in the chamber was considered to be porous matter with a quadratic law of resistance,this is in accordance with the manufacturer's data that were verified with pressure-loss measurements.
Keywords: komore lakirne; dinamika tekočin; analize numerične; turbulenca; automotive industry; avtomobilska industrija; lakiranje; tok tekočin; numerična analiza